Dietary supplementation with a wild green oat extract (Avena sativa L.) to improve wellness and wellbeing during smoking reduction or cessation: a randomized double-blind controlled study - Friling, Marina; García-Muñoz, Ana María; Lavie, Arava; Pérez-Piñero, Silvia; Victoria-Montesinos, Desirée; López-Román, Francisco Javier; García-Guillén, Ana Isabel; Muñoz-Carrillo, Juan Carlos; Cánovas, Fernando; Ivanir, Eran; Jalanka, Jonna (Frontiers in Nutrition, 2024)
Objective Smoking reduction or cessation are critical public health goals, given the well-documented risks of tobacco use to health. Reducing smoking frequency and cessation entirely are challenging due to nicotine addiction and withdrawal symptoms, which can significantly affect mental wellness and overall wellbeing. Previous research has suggested that certain dietary supplements may support smoking cessation and reduction efforts by mitigating these adverse effects. The objective of this study was to assess the effect of supplementation with 900 mg/day of Neuravena®, a green oat extract (GOE) of Avena sativa L., in enhancing wellness and wellbeing during a smoking reduction or cessation experience. Methods This was an 8-week randomized, double-blind, placebo-controlled study, ClinicalTrials Identifier: NCT04749017 (https://classic.clinicaltrials.gov/ct2/show/NCT04749017). Participants were assigned to one of the study groups, 72 participants were assigned to GOE and 73 to placebo. The subjects were followed for 8-weeks intervention period as well as an additional 4-week follow-up period. At subsequent visits, they underwent clinical assessments including assessments of quality of life, perceived stress, depression, nicotine dependence, anxiety, cognitive performance, and specific assessments of craving intensity. Results GOE was associated with greater improvements in elements of the abbreviated World Health Organization Quality of Life (WHOQOL-BREF) questionnaire as compared with placebo. Similar results were obtained from the SF-36 questionnaire and a visual QoL analogue scale (VAS). Perceived stress levels showed greater decline from baseline among the GOE supplemented participants as compared to placebo. Sleep quality parameters improved with GOE supplementation and worsened in the placebo group. At the end of the intervention period, the percentage of successful reducers (defined as >20% reduction in daily cigarettes) was higher in the GOE group as compared to placebo (66.7% vs. 49.3%, p = 0.034). The improvements from baseline in QoL measures in the GOE group persisted at 4 weeks after termination of the intervention. Conclusion GOE supplementation demonstrated greater improvements in quality of life measures, stress and sleep related parameters during a smoking reduction or cessation experience and the product was shown to be safe and well tolerated.